Legal Aspects and Issues of Blockchain Implementation as The Technology Base of Smart Contract - Qur’ani Dewi Kusumawardani; M. Hawin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Blockchain, as a supporting technology for the industrial revolution 4.0, has excellent potential to change many areas of private legal transactions, including as the technological basis of smart contracts. The application of blockchain technology has its own legal aspects, risks, legal issues and challenges to provide regulatory policies to optimize the technology's potential and simultaneously mitigate risks. This research aims, firstly, to discover the legal aspects that should be considered in blockchain technology and, secondly, the legal issues of implementing blockchain technology, especially those related to finance, jurisdiction, and cyber-attacks. The research method to be used is normative legal research. The research results obtained are, first, the aspect of the existence of the law itself, which is related to binary code through hash algorithms. Second, the legal issues of implementing blockchain in the financial sector are scalability, data privacy, data interoperability, and governance; related to jurisdiction related to the ability of blockchain to cross jurisdictional boundaries because nodes on the blockchain can transmit anywhere, in this world; related to cyber-attacks, namely brute force attacks on specific nodes which result in the dissemination of inaccurate information. Legal assistance and existence in technology (in this case, blockchain) are needed so that everything continues according to the rules to prevent more significant problems from arising.